2015
DOI: 10.5761/atcs.oa.13-00339
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Intraoperative Continuous Infusion of Tranexamic Acid during Emergency Surgery for Type A Acute Aortic Dissection

Abstract: IntroductionStanford type A acute aortic dissection is one of the diseases requiring emergency surgery. In acute aortic dissection, a large number of thrombi are rapidly formed in the false lumen immediately after onset, which activates the fibrinolytic system. Moreover, the surgery is performed using extracorporeal circulation with haparin, under hypothermic conditions. Both use of extracorporeal circulation and hypothermia are known to activate the fibrinolytic system. Thus, perioperative bleeding is a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…It has been certified that TXA can reduce blood loss and transfusion requirements effectively in cardiac [20] and non-cardiac surgical patients [21,22]. Similar results were obtained by Ahn et al [5] in a study which retrospectively studied data from 55 adult patients who underwent acute aortic dissection surgery between April 2008 and April 2010. Moreover, Makhija et al [7] also reported TXA had equal effect in reducing the perioperative bleeding and transfusion requirements in patients undergoing surgery for thoracic aortic compared with epsilonamino-caproic acid.…”
Section: Discussionsupporting
confidence: 70%
“…It has been certified that TXA can reduce blood loss and transfusion requirements effectively in cardiac [20] and non-cardiac surgical patients [21,22]. Similar results were obtained by Ahn et al [5] in a study which retrospectively studied data from 55 adult patients who underwent acute aortic dissection surgery between April 2008 and April 2010. Moreover, Makhija et al [7] also reported TXA had equal effect in reducing the perioperative bleeding and transfusion requirements in patients undergoing surgery for thoracic aortic compared with epsilonamino-caproic acid.…”
Section: Discussionsupporting
confidence: 70%
“…Our study showed that blood loss, not blood transfusion, was decreased in the high-dose group compared to the low-dose group. In acute aortic dissection, a large number of thrombi are rapidly formed in the false lumen immediately after onset, which activates the fibrinolytic system ( 18 ). Surgical factors also contribute to the activation of fibrinolytic system, such as aortic cross clamp ( 20 ), cardiopulmonary bypass ( 21 ), and hypothermia ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of tranexamic acid to reduce bleeding and transfusion rates was also demonstrated during off-pump coronary surgery (Wang et al, 2012), on-pump surgery while on dual antiplatelet therapy (Shi et al, 2013) and emergency surgery for type A acute aortic dissection (Ahn et al, 2015).…”
Section: Intra-operative Managementmentioning
confidence: 98%